The role of antidrug antibodies in ustekinumab therapy and the impact of methotrexate - Mojtahed Poor, Sorwe; Henke, Marina; Ulshöfer, Thomas; Köhm, Michaela; Behrens, Frank; Burkhardt, Harald; Schiffmann, Susanne (Rheumatology (Oxford, England), 2023)
Abstract Objective We investigated the impact of concomitant MTX on ustekinumab (UST) levels and antidrug antibody (ADA) formation in PsA and evaluated consequences in pharmacodynamics and pharmacokinetics. Methods We conducted a post-hoc analysis on 112 PsA serum samples of subjects treated with open-label UST and either concomitant MTX (UST/MTX, n = 58) or placebo (UST/pbo, n = 54) obtained in a randomized (1:1), double-blind, multicentre trial. A validated antibody-binding-based multitiered testing was used to detect ADA and ADA with neutralizing capacity (nADA). The impact of MTX on UST immunogenicity was analysed by comparison of UST/pbo with UST/MTX cohorts at different time points. Patient- and disease-related predispositions for ADA formation were investigated with multiple linear regression analysis. Immunogenicity impact on pharmacokinetics, safety and efficacy was determined by cohort comparison between patients with and without ADA formation. Results Over 52 weeks, 11 UST/pbo- and 19 UST/MTX-treated patients developed ADA (P > 0.05). In the UST/pbo cohort, the visit-dependent UST levels were in the range of 0.047 (0.05) –0.110 (0.07) µg/ml overall, and 0.037 (0.04)–0.091 (0.08) µg/ml in ADA-confirmed subjects. In UST/MTX-treated patients, the UST levels exhibited an intervisit variation in the range of 0.0502 (0.04)–0.106 (0.07) µg/ml overall and 0.029 (0.03)–0.097 (0.07) µg/ml in ADA positive subjects (P > 0.05). At week 52, ADA-confirmed patients did not differ significantly (P > 0.05) in safety or clinical outcomes from ADA-negative patients. Conclusion Concomitant MTX had no significant impact on UST immunogenicity. Furthermore, ADA formation was not associated with impairments in UST safety, efficacy or trough levels. Trial registration ClinicalTrials.gov, https://clinicaltrials.gov, NCT03148860.